Behaviorism and humanistic psychology: Two views of human nature in an indidualistic society - KATILIŪTĖ - BOYDSTUN, D. (Psichologija, 1997)
The article outlines the philosophical antecedents of behaviorism and humanistic psychology, discussing those aspects of each theoretical position that focus on personality and imply a certain view of human nature. If also discusses the philosophical flaws of each aspect and describes the formal applications of each theory in the United States, discussing the impact of the two implied views of human nature of American society, and suggesting that they have both enjoyed such ready acceptance because they are complementary aspects of an underlying individualistic world-view. Finally, it examines some evidence of such views existing or emerging in post-Soviet Lithuania.